Weighted minimal affine translation surfaces in Euclidean space with density - Yoon, Dae Won; Yuzbasi, Zuhal Kucukarslan (World Scientific Publ Co Pte Ltd, 2018)
The aim of this work is to study affine translation surfaces in the Euclidean 3-space with density. We completely classify affine translation surfaces with zero weighted mean curvature.
Keywords: Affine translation surface; manifold with density; weighted mean curvature